1998
DOI: 10.1017/s1461145798001242
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind, placebo-controlled, crossover trial of D-cycloserine adjuvant therapy for treatment-resistant schizophrenia

Abstract: Dysfunction of N-methyl-D-aspartate (NMDA) receptor-mediated glutamatergic neurotransmission may be relevant to the pathogenesis of negative symptoms in schizophrenia. The tuberculostatic compound D-cycloserine (DCS) acts as a partial agonist at the strychnine-insensitive glycine regulatory site on the NMDA receptor complex. Dose-finding trials suggest that DCS doses of 50-100 mg/d may be beneficial in the treatment of negative symptoms in schizophrenia. Nine treatment-resistant chronic schizophrenic patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 0 publications
0
31
1
Order By: Relevance
“…More recent theories have suggested alternative use of drugs targeted at the NMDA receptor (Javitt, 2001;Javitt and Zukin, 1991). 'First-generation' agents that have been used in clinical studies include both glycine (Heresco-Levy et al, 2004;Heresco-Levy et al, 1999;Javitt et al, 2001;Javitt et al, 1994) and D-serine (Tsai et al, 1998), which are endogenous agonists, as well as the synthetic glycine/D-serine derivative D-cycloserine, which is a partial agonist (Goff et al, 1999;Heresco-Levy et al, 1998). Development of high-affinity glycine-site agonists, however, is limited by the small molecular size of the target (McBain et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…More recent theories have suggested alternative use of drugs targeted at the NMDA receptor (Javitt, 2001;Javitt and Zukin, 1991). 'First-generation' agents that have been used in clinical studies include both glycine (Heresco-Levy et al, 2004;Heresco-Levy et al, 1999;Javitt et al, 2001;Javitt et al, 1994) and D-serine (Tsai et al, 1998), which are endogenous agonists, as well as the synthetic glycine/D-serine derivative D-cycloserine, which is a partial agonist (Goff et al, 1999;Heresco-Levy et al, 1998). Development of high-affinity glycine-site agonists, however, is limited by the small molecular size of the target (McBain et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…An interaction between clozapine and the a7* nicotinic receptor is supported by the demonstration of a clozapine-induced release of acetylcholine in the prefrontal cortex (Ichikawa et al, 2002). In favor of an interaction by clozapine with glutamatergic mechanisms, treatment augmentation studies with agents acting at the glycine-site of the NMDA receptor have shown that glycine and Dcycloserine improve negative symptoms when added to conventional antipsychotic drugs, but not when added to clozapine (Evins et al, 2002;Goff et al, 1999, Heresco-Levy et al, 1998Javitt et al, 1994;Tsai et al, 1998). This indicates that clozapine may be an agonist or partial agonist at the glycine-site of the NMDA receptor or an inhibitor of the glycine transporter and such actions may contribute to its unique clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies, some of them double blind and placebo-controlled, have shown that d-cycloserine, glycine, and d-serine improve some aspects of negative symptomatology and cognitive dysfunction, do not interfere with the beneficial effects of antipsychotics on the positive symptomatology and are also well tolerated (Goff et al, 1995(Goff et al, , 1999Tsai et al, 1998;Heresco-Levy et al, 1998, 2002Javitt et al, 2001;Evins et al, 2002). Beneficial effects on negative symptomatology and cognitive dysfunction are of interest, as current antipsychotics are marginally effective against these two aspects of the pathology.…”
Section: Introductionmentioning
confidence: 99%